Toner and its manufacturing method
A toner with a hardened oil having a specific melting point and crystal structure addresses UFP generation and low-temperature fixing issues, enhancing safety and energy efficiency in electrophotographic devices.
Patent Information
- Application Number
- JP2023213411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-18
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2039-03-29
AI Technical Summary
Existing toners generate ultrafine particles (UFP) due to the sublimation of low-melting point waxes, posing health risks and requiring high-temperature fixing, which is inefficient and undesirable in energy-conscious devices.
A toner formulation using a highly hardened oil with a melting point between 50°C and 80°C, produced through a deodorizing process, and containing β-type crystals with a particle size of less than 30 μm, is incorporated into the toner manufacturing process to enhance low-temperature fixability and reduce UFP generation.
The solution effectively reduces UFP generation while maintaining low-temperature fixability, minimizing health hazards and improving energy efficiency in multifunction devices and printers.
Smart Images

Figure 0007600358000001 
Figure 0007600358000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing, etc., and to a method for producing the toner. The present invention also relates to a wax composition for a toner and an agent for reducing ultrafine dust particles. [Background technology]
[0002] In order to save energy, multifunction devices and printers used in offices are required to have toners that can be fixed at low temperatures. It has long been known that a low-melting wax can be used in combination with the toner to fix it at low temperatures (Patent Document 1).
[0003] On the other hand, it is also well known that ultrafine particles (hereinafter, also referred to as UFP) are generated from toner wax in multifunction devices and printers (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 8-278657 [Patent Document 2] JP 2017-167524 A Summary of the Invention [Problem to be solved by the invention]
[0005] Low-melting wax partially sublimes when heated, turning into ultrafine particles (UFP), which is a concern for the health of users. Therefore, a toner that combines low-temperature fixing properties and UFP reduction was required.
[0006] An object of the present invention is to provide a toner capable of achieving low-temperature fixability and reducing UFP. [Means for solving the problem]
[0007] The present invention may include the following aspects. [1] A method for producing a toner having excellent resistance to in-machine contamination, comprising a step of melting and kneading a binder resin and a release agent, the release agent containing extremely hardened oil having a melting point of 50°C or more and less than 80°C (excluding hardened oils having an erucic acid content of 40% by weight or more of total fatty acids), the extremely hardened oil being produced through a deodorizing step, the extremely hardened oil containing a fat powder having β-type crystals, and the fat powder having an average particle size of less than 30 μm. [2] The method for producing a toner having excellent resistance to in-machine contamination according to [1], wherein the content of the extremely hardened oil in the toner is 1 to 10 parts by weight per 100 parts by weight of a binder resin. [3] An ultrafine dust reducing agent for toner, which contains as an active ingredient extremely hardened oil having a melting point of 50°C or more and less than 80°C (excluding hardened oils in which the erucic acid content is 40% by weight or more of the total fatty acids) and is produced through a deodorizing process, characterized in that the extremely hardened oil contains oil powder having β-type crystals and the average particle size of the oil powder is less than 30 μm. [4] A method for producing a toner having excellent resistance to in-machine contamination, comprising a step of melting and kneading a binder resin and a release agent, the release agent comprising the ultrafine particle dust reducing agent for toner according to [3]. [5] The method for producing a toner having excellent resistance to in-machine contamination according to [4], wherein the content of the ultrafine particle dust reducing agent for toner in the toner is 1 to 10 parts by weight per 100 parts by weight of binder resin. Effect of the Invention
[0008] According to the present invention, it is possible to improve low-temperature fixing ability and reduce the generation of UFP, thereby reducing the amount of toner remaining in the toner cartridge, and also to reduce the possibility of health hazards for users of multifunction devices and printers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The toner of the present invention is a toner containing a binder resin and a release agent, the release agent containing extremely hardened oil having a melting point of 50°C or more and less than 80°C, and the extremely hardened oil is produced through a deodorization process.
[0010] As a result of intensive research, the present inventors have found that the above-mentioned release agent exhibits low-temperature fixing performance while also significantly reducing UFP. The reason for this is unclear, but it is thought to be, for example, as follows. Note that this is explained in order to make the principle of the present invention easier to understand, and the present invention is not restricted by this principle. The release agent used in the present invention contains extremely hardened oil with a melting point of 50°C or more but less than 80°C, so it melts appropriately even at low temperatures and can improve low-temperature fixability. In addition, because the release agent uses extremely hardened oil that has been produced through a deodorizing process, some of the substances that could become dust are removed in the deodorizing process, which is presumably what makes it possible to reduce the generation of UFPs when used in multifunction devices and printers.
[0011] The toner manufacturing method of the present invention is characterized in that it includes a step of melting and kneading at least a binder resin and a release agent, the release agent contains extremely hardened oil having a melting point of 50°C or more and less than 80°C, and the extremely hardened oil has been subjected to a deodorizing step.
[0012] <Binding resin> The binder resin used in the present invention preferably contains polyester from the viewpoint of excellent low-temperature fixing property, storage stability and durability of the toner. The content of polyester in the binder resin is preferably 80% by weight or more, more preferably 90% by weight or more, and it is further preferable to use only polyester as the binder resin, but other resins other than polyester may be contained within a range in which the effect of low-temperature fixing property is not impaired. Examples of other binder resins include vinyl resins, epoxy resins, polycarbonates, polyurethanes, etc.
[0013] The polyester used in the present invention can be obtained by condensation polymerization of an alcohol component consisting of a dihydric or higher alcohol and a carboxylic acid component consisting of a dihydric or higher carboxylic acid compound.
[0014] Examples of the dihydric alcohol include diols having 2 to 20 carbon atoms, preferably 2 to 15 carbon atoms, and diols represented by the formula (I):
[0015] [ka]
[0016] (In the formula, RO and OR are oxyalkylene groups, R is an ethylene and / or propylene group, x and y represent the number of moles of alkylene oxide added and are each a positive number, and the average value of the sum of x and y is preferably 1 to 16, more preferably 1 to 8, and further preferably 1.5 to 4.) Examples of the dihydric alcohol having 2 to 20 carbon atoms include ethylene glycol, propylene glycol, 1,4-butanediol, 1,6-hexanediol, bisphenol A, hydrogenated bisphenol A, and the like.
[0017] From the viewpoint of reducing the amount of toner remaining in the toner cartridge, the alcohol component is preferably an alkylene oxide adduct of bisphenol represented by formula (I). The content of the alkylene oxide adduct of bisphenol represented by formula (I) in the alcohol component is preferably 50 mol% or more, more preferably 70 mol% or more, even more preferably 90 mol% or more, and even more preferably substantially 100 mol%.
[0018] Examples of the trihydric or higher alcohol include polyhydric trihydric or higher alcohols having 3 to 20 carbon atoms, preferably 3 to 10 carbon atoms. Specific examples include sorbitol, 1,4-sorbitan, pentaerythritol, glycerol, and trimethylolpropane.
[0019] Examples of the divalent carboxylic acid compound include dicarboxylic acids having 3 to 30 carbon atoms, preferably 3 to 20 carbon atoms, and more preferably 3 to 10 carbon atoms, and their derivatives such as acid anhydrides and alkyl (having 1 to 4 carbon atoms) esters. Specific examples include aromatic dicarboxylic acids such as phthalic acid, isophthalic acid, and terephthalic acid, and aliphatic dicarboxylic acids such as fumaric acid, maleic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, and succinic acid substituted with an alkyl or alkenyl group having 1 to 20 carbon atoms.
[0020] Examples of the trivalent or higher carboxylic acid compound include trivalent or higher polyvalent carboxylic acids having 4 to 30 carbon atoms, more preferably 4 to 20 carbon atoms, and even more preferably 4 to 10 carbon atoms, and their derivatives such as acid anhydrides and alkyl (1 to 4 carbon atoms) esters. Specific examples include 1,2,4-benzenetricarboxylic acid (trimellitic acid), 1,2,4,5-benzenetetracarboxylic acid (pyromellitic acid), etc.
[0021] From the viewpoint of adjusting the softening point of the polyester, the alcohol component may appropriately contain a monohydric alcohol, and the carboxylic acid component may appropriately contain a monovalent carboxylic acid compound.
[0022] The equivalent ratio (COOH group / OH group) of the carboxylic acid component to the alcohol component in the polyester is preferably from 0.70 to 1.00, and more preferably from 0.75 to 0.95, from the viewpoint of reducing the acid value of the polyester.
[0023] The polycondensation reaction between the alcohol component and the carboxylic acid component can be carried out in an inert gas atmosphere, in the presence of an esterification catalyst, an esterification promoter, a polymerization inhibitor, etc., as necessary, by polycondensation at a temperature of about 180 to 250°C. Examples of the esterification catalyst include tin compounds such as dibutyltin oxide and tin(II) 2-ethylhexanoate, and titanium compounds such as titanium diisopropylate bistriethanol aminate, and examples of the esterification promoter include gallic acid. The amount of the esterification catalyst used is preferably 0.01 to 1.5 parts by weight, more preferably 0.1 to 1.0 parts by weight, based on 100 parts by weight of the total amount of the alcohol component and the carboxylic acid component. The amount of the esterification promoter used is preferably 0.001 to 0.5 parts by weight, more preferably 0.01 to 0.1 parts by weight, based on 100 parts by weight of the total amount of the alcohol component and the carboxylic acid component.
[0024] The softening point of the polyester is preferably 90 to 140°C, more preferably 100 to 135°C, and further preferably 105 to 125°C, from the viewpoint of reducing the amount of toner remaining in the toner cartridge and improving the low-temperature fixing property and high-temperature offset resistance of the toner.
[0025] From the viewpoint of improving low-temperature fixing ability and high-temperature offset resistance, the binder resin used in the present invention preferably contains two types of polyesters having different softening points.
[0026] The difference in softening point between the polyester with a higher softening point and the polyester with a lower softening point is preferably 10° C. or more, more preferably 10 to 30° C., from the viewpoint of improving the low-temperature fixability and high-temperature offset resistance of the toner.
[0027] The softening point of the polyester can be controlled by adjusting the types and composition ratios of the alcohol component and carboxylic component, the amount of catalyst, and by selecting reaction conditions such as reaction temperature, reaction time, and reaction pressure.
[0028] The glass transition point of the polyester is preferably from 50 to 80° C., more preferably from 60 to 70° C., from the viewpoint of reducing the amount of toner remaining in the toner cartridge and improving the low-temperature fixability and storage stability of the toner.
[0029] The glass transition point of the polyester can be controlled by the types and composition ratios of the alcohol and carboxylic components.
[0030] When a plurality of polyesters are used, it is preferable that the weighted average softening point and glass transition point of the polyester are within the above range.
[0031] From the viewpoint of reducing the amount of toner remaining in the toner cartridge, the acid value of the polyester is preferably 30 mgKOH / g or less, and more preferably 20 mgKOH / g or less.
[0032] The acid value of the polyester can be controlled by adjusting the types and composition ratios of the alcohol component and carboxylic component, the amount of catalyst, and by selecting reaction conditions such as reaction temperature, reaction time, and reaction pressure.
[0033] In the present invention, the polyester may be modified to such an extent that its properties are not substantially impaired. Modified polyesters include polyesters grafted or blocked with phenol, urethane, epoxy, or the like by the methods described in, for example, JP-A-11-133668, JP-A-10-239903, JP-A-8-20636, and the like.
[0034] <Release agent> The release agent used in the present invention is characterized in that it contains extremely hardened oil having a melting point of 50° C. or more and less than 80° C., and the extremely hardened oil is produced through a deodorizing process. The extremely hardened oil, which is one of the components of the release agent, will be explained step by step below.
[0035] <Extremely hydrogenated oil> The extremely hardened oil of the present invention is not particularly limited as long as it has a melting point of 50°C or more and less than 80°C. Examples include extremely hardened rapeseed oil, extremely hardened high erucic acid rapeseed oil, extremely hardened sunflower oil, extremely hardened safflower oil, and extremely hardened palm oil. These extremely hardened oils may be used alone or in combination of two or more. The melting point is preferably 55°C or more and less than 75°C, more preferably 57°C or more and less than 73°C, and even more preferably 60°C or more and less than 70°C. When the melting point of the oil as the raw material of the oil powder is within the above range, the toner is likely to exhibit low-temperature fixability. The melting point can be measured in accordance with "Standard Oil Analysis Test Method 2.2.4.2-1996 of the Japan Oil Chemists' Society".
[0036] <Raw material oils for extremely hardened oils> The raw material fats and oils of the extremely hardened oil of the present invention are not particularly limited as long as they have a melting point of 50°C or more and less than 80°C after the hardening treatment described below. Here, the raw material fats and oils refer to fats and oils before hardening treatment (hydrogenation) for producing the extremely hardened oil. The raw material fats and oils are not particularly limited as long as they are edible fats and oils, and examples of the raw material fats and oils include coconut oil, palm oil, palm kernel oil, milk fat, lard, beef tallow, soybean oil, rapeseed oil, high erucic rapeseed oil (high erucic acid rapeseed oil), corn oil, sunflower oil, safflower oil, sesame oil, cottonseed oil, rice oil, olive oil, peanut oil, and linseed oil, and a mixture of these oils may be used as the raw material fats and oils.
[0037] <Hardening treatment> The method of hardening (hydrogenation) performed on the above-mentioned raw oil and fat is not particularly limited, and can be performed by a conventional method. Hydrogenation can be performed, for example, under conditions of a hydrogen pressure of 0.02 to 0.3 MPa and a temperature of 160 to 230° C. in the presence of a nickel catalyst. In the present invention, the extent of hardening (hydrogenation) is arbitrary, but in order to reduce the generation of UFP, it is preferable to reduce the content of unsaturated fatty acids, so that it is preferable to extremely hydrogenate, for example, until the iodine value is about 0 to 4. That is, the iodine value of the extremely hardened oil of the present invention is preferably less than 4, more preferably less than 2, and even more preferably less than 1. The iodine value of the oil and fat can be measured according to "Standard Method for Analysis of Fats, Oils, and Related Materials 2.3.4.1-1996, Japan Oil Chemists' Society".
[0038] <Deodorization process> The deodorization step performed on the extremely hardened oil that has been subjected to the above-mentioned hardening treatment is not particularly limited as long as it is performed under conditions that are usually adopted in the refining method of edible oils and fats. For example, the temperature condition of the deodorization step is 220 to 260°C (preferably 240 to 260°C). The pressure condition of the deodorization step is reduced pressure (vacuum degree of 200 to 600 Pa, preferably 250 to 600 Pa). In the deodorization step, 2 to 5% by weight of steam is blown into the extremely hardened oil under the above-mentioned temperature and pressure conditions to deodorize the extremely hardened oil. The deodorization time is preferably 10 to 150 minutes, more preferably 30 to 100 minutes. By deodorizing the extremely hardened oil under the above-mentioned conditions, a deodorized extremely hardened oil can be obtained. The apparatus used in the deodorizing step is not particularly limited, and may be a tray-type apparatus or the like used in the production of ordinary deodorized oil. In the present invention, the "degree of vacuum" is expressed in terms of absolute pressure. This value indicates how close the vacuum is to an ideal vacuum state (absolute vacuum), with an absolute vacuum being zero.
[0039] <2-chain length β type crystal> The above-mentioned extremely hardened oil preferably further contains a fat powder having a 2-chain length β-type crystal. Here, the fat crystal having a 2-chain length is determined by measuring the long plane spacing of the fat crystal by X-ray diffraction. That is, the long plane spacing of the fat crystal is measured in the range of 2θ of 0 to 8 degrees. At this time, when a diffraction peak corresponding to 40 to 50 Å is detected and a diffraction peak corresponding to 60 to 65 Å is not detected, or even if detected, the diffraction intensity of the diffraction peak corresponding to 40 to 50 Å is less than 1 / 5 (preferably less than 1 / 10), the fat crystal is determined to have a 2-chain length structure. Here, the β-type is one of the crystal polymorphs of fats and oils. Some fats and oils have the same composition but different sublattice structures (crystal structures), and are called crystal polymorphs. Representative types include hexagonal type, orthorhombic perpendicular type, and triclinic parallel type, which are called α-type, β'-type, and β-type, respectively. Here, the crystal form of the fat crystals is β type when the fat crystals have a diffraction peak at 4.5 to 4.7 Å, preferably at around 4.6 Å, in an X-ray diffraction measurement with 2θ of 17 to 26 degrees, and in particular, have no diffraction peak at 4.1 to 4.3 Å, preferably at around 4.2 Å. More specifically, in the X-ray diffraction measurement, the ratio of the peak intensity at around 2θ=19° (4.6 Å), which is a characteristic peak of the β type, to the peak intensity at around 2θ=21° (4.2 Å), which is a characteristic peak of the α type (and β' type), 19° / (19°+21°)[4.6 Å / (4.6 Å+4.2 Å)] can be calculated as an index representing the amount of β type crystals present. In the present invention, the peak intensity ratio is preferably 1. However, the lower limit of the peak intensity ratio may be, for example, 0.4 or more, preferably 0.5 or more, more preferably 0.6 or more, even more preferably 0.7 or more, particularly preferably 0.75 or more, and most preferably 0.8 or more. If the peak intensity ratio is 0.4 or more, more than 50% by weight of the fat and oil crystals can be considered to be β type. The upper limit of the peak intensity ratio is preferably 1, but may be 0.99 or less, 0.98 or less, 0.95 or less, 0.93 or less, 0.90 or less, 0.85 or less, 0.80 or less, etc. The peak intensity ratio may be any one of the above lower limit and upper limit values, or any combination.When the fat crystals of the fat powder are of the double-chain length β type (peak intensity ratio within the above range), they effectively function as double-chain length β type crystal seeds.
[0040] Here is a supplementary explanation of the X-ray diffraction method for identifying the crystal polymorphism of the above-mentioned fats and oils. The diffraction conditions are given by the following Bragg equation. 2dsinθ=nλ(n=1,2,3...) A diffraction peak appears at a position that satisfies this formula. Here, d is the lattice constant, θ is the diffraction (incidence) angle, λ is the wavelength of the X-ray, and n is a natural number. From the diffraction peak corresponding to the short spacing at 2θ=16 to 27°, information on the packing of the side surfaces (sublattice) in the crystal can be obtained, and the polymorph can be identified. In particular, in the case of triacylglycerol, a characteristic peak of the β type appears at 2θ=19, 23, and 24° (near 4.6 Å, near 3.9 Å, near 3.8 Å), and a characteristic peak of the α type appears at around 21° (4.2 Å). Note that the X-ray diffraction measurement is performed, for example, using an X-ray diffraction device (for example, Rigaku Corporation, horizontal sample type X-ray diffraction device UItimaIV) maintained at 20°C. CuKα radiation (1.54 Å) is most commonly used as the source of X-rays. In the intensity analysis of the diffraction peak obtained by the X-ray diffraction measurement, it is appropriate to perform a correction to remove the effect of the amorphous part of the oil on the baseline. For example, background removal processing may be performed using the Sonneveld-Visser method.
[0041] <Average particle size> The fat and oil powder preferably has an average particle size of 50 μm or less. The average particle size of the fat and oil powder is preferably less than 30 μm, more preferably less than 20 μm, and even more preferably less than 15 μm. The average particle size (effective diameter) is a value (d50) measured by a laser diffraction scattering method (ISO133201, ISO9276-1) using a particle size distribution measuring device (e.g., Microtrac MT3300ExII manufactured by Nikkiso Co., Ltd.). The effective diameter means the particle size of a sphere when the measured diffraction pattern of the fat and oil powder to be measured matches the theoretical diffraction pattern obtained assuming a sphere. In this way, in the case of the laser diffraction scattering method, the effective diameter is calculated by matching the theoretical diffraction pattern obtained assuming a sphere with the measured diffraction pattern, so that the measurement can be performed according to the same principle whether the measurement object has a plate-like shape or a spherical shape.
[0042] <Plate shape> Furthermore, as one of the preferred aspects of the oil and fat powder, for example, the oil and fat powder particles have a plate-like shape (are plate-like). Here, the plate-like shape has an aspect ratio of preferably 1.2 or more. The aspect ratio is more preferably 1.2 to 3.0, even more preferably 1.3 to 2.5, and even more preferably 1.4 to 2.0. The aspect ratio here is defined as the ratio of the long side length to the short side length of a rectangle circumscribing the particle figure so as to minimize the area. Therefore, when the particles have a spherical shape, the aspect ratio is smaller than 1.1. In the conventional method of dissolving oils and fats having a high solid fat content at room temperature, such as extremely hardened oils, and directly spraying the same, the oil and fat powder particles have a spherical shape due to surface tension, and the aspect ratio is approximately less than 1.1. The aspect ratio can be determined, for example, by directly observing arbitrarily selected particles using an optical microscope or a scanning electron microscope, measuring the length in the major axis direction and the length in the minor axis direction, and calculating the average value of the number of particles measured.
[0043] <Loose bulk density> A preferred embodiment of the oil powder is one having a loose bulk density of 0.05 to 0.6 g / cm3. When the powdered oil composition is substantially composed of oil powder, the loose bulk density is preferably 0.1 to 0.5 g / cm3, more preferably 0.1 to 0.4 g / cm3 or 0.15 to 0.4 g / cm3, and even more preferably 0.2 to 0.3 g / cm3. Here, the "loose bulk density" is the packing density of the powder in a state where the powder is allowed to fall naturally. The loose bulk density (g / cm3) can be measured, for example, by dropping an appropriate amount of the powdered oil composition into a measuring cylinder having an inner diameter of 15 mm x 25 mL from about 2 cm above the upper opening end of the measuring cylinder to loosely pack the mixture, measuring the weight (g) of the mixture and reading the volume (mL), and calculating the weight (g) of the powdered oil composition per mL. The loose bulk density can also be calculated from the bulk density measured based on JIS K-6720 (or ISO 1060-1 and 2) using a bulk density measuring device manufactured by Kuramochi Scientific Instruments Manufacturing Co., Ltd. Specifically, 120 mL of sample is dropped into a receiver (a 100 mL cylindrical container with an inner diameter of 40 mm and a height of 85 mm) from a position 38 mm above the upper opening of the receiver. The sample that rises from the receiver is scraped off, and the weight (Ag) of the sample equivalent to the internal volume (100 mL) of the receiver is measured, and the loose bulk density can be calculated from the following formula. Loose bulk density (g / mL) = A(g) / 100(mL) It is preferable to carry out the measurement three times and take the average value.
[0044] <Method of manufacturing oil and fat powder> The method for producing the above-mentioned oil and fat powder is not particularly limited, and conventionally known methods such as freeze pulverization, extrusion granulation, spray cooling granulation, etc. may be applied. However, one of the preferred embodiments in which the extremely hardened oil having a melting point of 50° C. or more and less than 80° C. is used as the oil and fat powder of the present invention is an embodiment in which the extremely hardened oil having a melting point of 50° C. or more and less than 80° C. contains one or more XXX-type triglycerides having fatty acid residues X with carbon number x at positions 1 to 3 of glycerin, and the carbon number x is an integer selected from 14 to 22.
[0045] The XXX type triglycerides contained in the above-mentioned oils and fats with a melting point of 50°C or higher are glycerin and each fatty acid residue X has a carbon number x at the 1st to 3rd positions of are the same as each other. Here, the number of carbon atoms x is an integer selected from 14 to 22, and preferably Preferably, an integer selected from 16 to 22, more preferably an integer selected from 16 to 20. and more preferably an integer selected from 16 to 18. The fatty acid residue X is a saturated or may be an unsaturated fatty acid residue. Specific examples of the fatty acid residue X include myris Examples include acetic acid, palmitic acid, stearic acid, arachidic acid, and behenic acid residues. However, the fatty acid residue X is not limited thereto. More preferably, the fatty acid residue X is palladium. Among these, preferred are glycerin, glycerin, glycerin, glycerol ... tric acid, stearic acid, and arachidic acid, and especially preferred are palmitic acid and Acid and stearic acid. The content of the XXX type triglyceride contained in the extremely hardened oil having a melting point of 50°C or more and less than 80°C is, when the total weight of the extremely hardened oil is taken as 100% by weight, for example, 50% by weight or more, preferably 60% by weight or more, more preferably 70% by weight or more, and even more preferably 80% by weight or more as the lower limit, and for example, 100% by weight or less, preferably 99% by weight or less, and more preferably 95% by weight or less as the upper limit. One or two or more types of XXX type triglyceride can be used, preferably one or two types, and more preferably one type is used. When there are two or more types of XXX type triglyceride, the total value is the content of the XXX type triglyceride.
[0046] The above-mentioned extremely hardened oil having a melting point of 50°C or more and less than 80°C may contain other triglycerides other than the above-mentioned XXX triglycerides. The other triglycerides may be a plurality of types of triglycerides, and may be synthetic or natural oils and fats. Examples of natural oils and fats include palm oil, cocoa butter, sunflower oil, rapeseed oil, soybean oil, and cottonseed oil. When the above-mentioned extremely hardened oil having a melting point of 50°C or more and less than 80°C is taken as 100% by weight, there is no problem even if the other triglycerides other than the above-mentioned XXX triglycerides are contained in an amount of 1% by weight or more, for example, about 5 to 50% by weight. The content of the other triglycerides is, for example, preferably 0 to 30% by weight, more preferably 0 to 18% by weight, even more preferably 0 to 15% by weight, and even more preferably 0 to 8% by weight.
[0047] The above-mentioned extremely hardened oil having a melting point of 50°C or more and less than 80°C and containing XXX triglycerides can be melted and then kept at a specific cooling temperature to solidify, thereby obtaining a fat powder without employing special processing means such as spraying or mechanical pulverization with a pulverizer such as a mill. More specifically, (a) the above-mentioned extremely hardened oil having a melting point of 50°C or more and less than 80°C and containing XXX triglycerides is prepared, and optionally, in step (b), the extremely hardened oil obtained in step (a) is heated to melt the triglycerides contained in the extremely hardened oil to obtain the extremely hardened oil in a molten state, and further (d) the extremely hardened oil in the molten state is cooled and solidified to obtain a fat powder containing double-chain length β-type crystals and having a plate-like particle shape.
[0048] The cooling in the step (d) may be carried out, for example, by subjecting the molten hardened oil to a temperature lower than the melting point of the hardened oil and satisfying the following formula: Cooling temperature (℃) = number of carbon x × 6.6 - 68 Cooling within this temperature range produces fine β-type fat crystals, making it easy to obtain fat powder.
[0049] In addition, between the above steps (b) and (d), an optional step for promoting powder production as step (c), such as (c1) a seeding step, (c2) a tempering step, and / or (c3) a preliminary cooling step, may be included. Furthermore, the fat powder obtained in the above step (d) may be obtained by a step (e) of pulverizing the solid obtained after the cooling in step (d) to obtain a fat powder.
[0050] In the above step (e), the solid obtained after cooling can be pulverized using a known pulverizing means such as a hammer mill or a cutter mill to produce an oil powder having an average particle size of 50 μm or less. In the above steps, the extremely hardened oil having a melting point of 50° C. or more and less than 80° C. and containing XXX triglycerides may be subjected to steps (a) to (e) in the form of a composition containing 0 to 15% by weight of components other than the above-mentioned oils and fats, or may be made into a β-type oil powder and then mixed with other components.
[0051] <Content in toner> The content of the extremely hardened oil in the toner is preferably 1 to 10 parts by weight relative to 100 parts by weight of the binder resin, from the viewpoint of reducing the amount of toner remaining in the toner cartridge and improving the low-temperature fixing property of the toner. Here, the content is preferably 2 parts by weight or more, more preferably 3 parts by weight or more, even more preferably 4 parts by weight or more, and most preferably 5 parts by weight or more. Also, from the viewpoint of reducing the amount of toner remaining in the toner cartridge and improving the storage stability of the toner, it is more preferably 8 parts by weight or less, even more preferably 7 parts by weight or less, and most preferably 6 parts by weight or less. In view of these viewpoints, the content of the extremely hardened oil in the toner is preferably 2 to 8 parts by weight, more preferably 3 to 7 parts by weight, and even more preferably 4 to 6 parts by weight relative to 100 parts by weight of the binder resin.
[0052] <Release agents other than hardened oils> The release agent used in the present invention may contain a release agent other than the extremely hardened oil, as long as the effect of the present invention is not impaired.
[0053] Examples of the release agent other than the above-mentioned extremely hardened oil include aliphatic hydrocarbon waxes such as low molecular weight polypropylene, low molecular weight polyethylene, low molecular weight polypropylene-polyethylene copolymer, microcrystalline wax, paraffin wax, Fischer-Tropsch wax, and oxides thereof; carnauba wax, montan wax, sazol wax, and deacidified waxes thereof; ester waxes such as fatty acid ester wax; fatty acid amides; and higher alcohols.
[0054] The content of the extremely hardened oil in the release agent is preferably 80% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and most preferably substantially 100% by weight.
[0055] <Toner> The toner of the present invention may also contain, as appropriate, colorants, charge control agents and other components that are used in ordinary toners.
[0056] <Coloring agent> As the colorant, any of the dyes, pigments, etc. used as toner colorants can be used. Specifically, carbon black, phthalocyanine blue, permanent brown FG, brilliant fast scarlet, pigment green B, rhodamine B base, solvent red 49, solvent red 146, solvent blue 35, quinacridone, carmine 6B, isoindoline, disazo yellow, etc. can be used.
[0057] The content of the colorant in the toner is preferably 1 to 40 parts by weight, and more preferably 2 to 10 parts by weight, per 100 parts by weight of the binder resin, from the viewpoint of improving image density and from the economic viewpoint.
[0058] <Charge control agent> As the charge control agent, either a negatively chargeable charge control agent or a positively chargeable charge control agent can be used.
[0059] Examples of the negatively charged charge control agent include metal-containing azo dyes such as "Bontron S-28" (manufactured by Orient Chemical Industry Co., Ltd.), "T-77" (manufactured by Hodogaya Chemical Industry Co., Ltd.), "Bontron S-34" (manufactured by Orient Chemical Industry Co., Ltd.), and "Aizenspiron Black TRH" (manufactured by Hodogaya Chemical Industry Co., Ltd.); copper phthalocyanine dyes; metal complexes of alkyl derivatives of salicylic acid such as "Bontron E-81", "Bontron E-84", and "Bontron E-304" (all manufactured by Orient Chemical Industry Co., Ltd.); nitroimidazole derivatives; benzilic acid boron complexes such as "LR-147" (manufactured by Nippon Carlit Co., Ltd.); and metal-free charge adjustment agents such as "Bontron F-21", "Bontron E-89" (all manufactured by Orient Chemical Industry Co., Ltd.), "T-8" (manufactured by Hodogaya Chemical Industry Co., Ltd.), "FCA-2521NJ", and "FCA-2508N" (all manufactured by Fujikura Chemical Industry Co., Ltd.).
[0060] Examples of the positively charged charge control agents include nigrosine dyes such as "Bontron N-01", "Bontron N-04", and "Bontron N-07" (all manufactured by Orient Chemical Industry Co., Ltd.) and "CHUO CCA-3" (manufactured by Chuo Synthetic Co., Ltd.); triphenylmethane dyes containing a tertiary amine as a side chain; quaternary ammonium salt compounds such as "Bontron P-51" (manufactured by Orient Chemical Industry Co., Ltd.), "TP-415" (manufactured by Hodogaya Chemical Co., Ltd.), cetyltrimethylammonium bromide, and "COPYCHARGEPXVP435" (manufactured by Clariant).
[0061] The content of the charge control agent in the toner is preferably 0.5 to 5 parts by weight, and more preferably 1 to 3 parts by weight, based on 100 parts by weight of the binder resin, from the viewpoint of improving the charge stability of the toner.
[0062] <Other ingredients> The toner obtained by the production method of the present invention may further contain other components, such as magnetic powder, a flowability improver, a conductivity adjuster, an extender pigment, a reinforcing filler such as a fibrous substance, an antioxidant, an antiaging agent, and a cleaning property improver, as appropriate.
[0063] <Toner manufacturing method> The toner of the present invention may be a toner obtained by any of the conventionally known methods such as a melt-kneading method, an emulsion aggregation method, a polymerization method, etc., but from the viewpoint of productivity, a pulverized toner obtained by a melt-kneading method is preferred. Therefore, the method for producing the toner of the present invention is preferably a method including a step of melt-kneading toner components including a binder resin containing polyester, a release agent, and a charge control agent to obtain a melt-kneaded product, and specifically, the toner components including a binder resin containing polyester, a release agent, a charge control agent, and additives such as a colorant used as necessary are uniformly mixed in a mixer such as a Henschel mixer, and then melt-kneaded, cooled, pulverized, and classified to produce a toner.
[0064] The melt-kneading of the toner components including the binder resin containing polyester, the release agent, the charge control agent, and additives such as a colorant used as necessary can be carried out using a known kneader such as an internal kneader, a single-screw or twin-screw kneader, an open roll type kneader, etc. From the viewpoint of reducing the temperature during melt-kneading and improving the low-temperature fixability and heat-resistant storage stability of the toner, and from the viewpoint of efficiently dispersing the toner components such as the release agent and the charge control agent in the binder resin to a high degree without repeating kneading or using a dispersion aid, it is preferable to use a twin-screw kneader.
[0065] A twin-screw kneader is a closed type kneader in which two kneading shafts are covered by a barrel, and it is preferable that the shafts rotate in the same direction. As a commercially available product, the PCM series twin-screw extruder manufactured by Ikegai Iron Works, which has good meshing of the two shafts at high speed, is preferable from the viewpoint of improving the productivity of toner.
[0066] It is preferable that the toner components, including the binder resin containing polyester, the release agent, the charge control agent, and additives such as a colorant used as needed, are mixed in advance in a mixer such as a Henschel mixer or a ball mill, and then supplied to the kneader.
[0067] The melt kneading in the twin-screw kneader is performed by adjusting the barrel set temperature (temperature of the inner wall surface of the extruder), the axial rotation speed of the twin screws, and the raw material supply speed. The barrel set temperature is preferably 80° C. or higher, more preferably 90° C. or higher, and is preferably 140° C. or lower, more preferably 120° C. or lower, from the viewpoint of improving the dispersibility of the release agent, charge control agent, etc. in the binder resin, and from the viewpoint of improving the productivity of the toner.
[0068] The peripheral speed of the two shafts is preferably 0.1 m / sec or more and 1.0 m / sec or less from the viewpoint of improving the dispersibility of the release agent, charge control agent, etc. in the binder resin and from the viewpoint of improving the productivity of the toner.
[0069] The feed rate of the raw materials to the twin-screw kneader is appropriately adjusted depending on the allowable capacity of the kneader used, the barrel set temperature, and the peripheral speed of the shaft rotation.
[0070] The obtained kneaded product is preferably cooled to a degree that allows pulverization, and then pulverized and classified. The pulverization process may be carried out in multiple stages. For example, the molten kneaded product may be coarsely pulverized to about 1 to 5 mm, and then finely pulverized to a desired particle size.
[0071] The pulverizer used in the pulverization step is not particularly limited. For example, pulverizers suitable for use in coarse pulverization include atomizers and rotoplexes, while pulverizers suitable for use in fine pulverization include jet mills, collision plate mills, and rotary mechanical mills.
[0072] Examples of classifiers used in the classification step include an air classifier, an inertial classifier, a sieve classifier, etc. In the classification step, the pulverized material removed due to insufficient pulverization may be subjected to the pulverization step again.
[0073] The release agent used in the toner manufacturing method of the present invention preferably contains extremely hardened oil having a melting point of 50° C. or more and less than 80° C., and the extremely hardened oil is preferably produced through a deodorizing process. Furthermore, the extremely hardened oil more preferably contains a fat powder having double-chain length β-type crystals, the fat powder further preferably has an average particle size of 50 μm or less, and the fat powder particles are most preferably in a plate shape with an aspect ratio of 1.2 or more. In the toner manufacturing method of the present invention, when the melt kneading method is adopted, if the above-mentioned extremely hardened oil (including oil powder having a plate-like shape) is used, it has good adhesion to the toner components including the binder resin containing polyester, other release agents, charge control agents, and additives such as colorants used as necessary, and when the toner components are melted in the melt kneading method, the above-mentioned extremely hardened oil may melt together and coat the other toner components well. This may be effective in reducing ultrafine particle dust (UFP), which is a feature of the present invention. Note that this mechanism is one example of the mechanism of the present invention, and the mechanism of the present invention is not limited thereto.
[0074] <Volume median particle size of toner base particles> The volume median particle size of the toner particles (D 50 From the viewpoint of improving the image quality of the toner, the volume median particle diameter (D 50 ) means the particle size at which the cumulative volume frequency calculated by volume fraction is 50% calculated from the smallest particle size.
[0075] <External Additive Processing Process> In the toner manufacturing method of the present invention, it is preferable to further include a step of mixing with an external additive, such as inorganic fine particles of silica or resin fine particles of polytetrafluoroethylene, after the pulverization and classification steps. For mixing the toner base particles and the external additives, it is preferable to use a mixer equipped with an agitator such as a rotating blade, and a high-speed mixer such as a Henschel mixer or a super mixer is preferable, with a Henschel mixer being more preferable.
[0076] The toner obtained by the production method of the present invention can be used as it is as a toner for one-component development, or as a toner for two-component development mixed with a carrier, in an image forming apparatus of a one-component development system or a two-component development system, respectively.
[0077] <Wax Composition for Toner> The toner wax composition of the present invention is characterized in that it contains a highly hydrogenated oil having a melting point of 50° C. or more and less than 80° C., and the highly hydrogenated oil is produced through a deodorizing process. Here, the extremely hardened oil having a melting point of 50° C. or more and less than 80° C. is as described above, and the deodorizing step is also as described above. The toner wax composition of the present invention can be produced by a known method. For example, the wax composition can be produced by adding other components to the extremely hardened oil, mixing them uniformly, cooling and solidifying the mixture, and pulverizing or granulating the mixture. As the other components, a release agent other than the extremely hardened oil can be used. In addition, since the melting point of the toner wax composition of the present invention is approximately the same as that of the extremely hardened oil, it is possible to impart low-temperature fixability to the toner. Furthermore, when the toner wax composition of the present invention is used as a toner wax, good image quality can be obtained. The toner wax composition of the present invention is mixed with a binder resin, a colorant, a charge control agent, etc., and a toner is produced by a conventional manufacturing method. The amount of the toner wax composition of the present invention mixed in the toner is 0.1 to 40 parts by weight based on 100 parts by weight of the binder resin.
[0078] <Ultrafine particle dust (UFP) reducing agent> As described above, the extremely hardened oil used in the present invention improves conventional toners to reduce the generation of ultrafine dust (UFP), and therefore the present invention also relates to an ultrafine dust reducing agent containing the extremely hardened oil as an active ingredient. As shown below, by blending the ultrafine dust reducing agent of the present invention with conventional toner raw materials, it is possible to achieve the effect of reducing the generation of ultrafine dust from toner. The ultrafine dust reducing agent of the present invention contains the above-mentioned extremely hardened oil. Since the ultrafine dust reducing agent of the present invention is effective even in small amounts, it contains preferably 60% by weight or more of the above-mentioned extremely hardened oil, more preferably 80% by weight or more, and even more preferably 100% by weight, when the agent is taken as 100% by weight. Furthermore, the ultrafine dust reducing agent of the present invention need only contain the extremely hardened oil described above as an active ingredient, and may also contain other excipients, other quality improvers and other ingredients within a range that does not impair the effects of the present invention. However, the preferred ultrafine dust reducing agent of the present invention is preferably substantially composed of the extremely hardened oil. Also, "substantially" means that the components other than the extremely hardened oil contained in the ultrafine dust reducing agent are, for example, 0 to 15% by weight, preferably 0 to 10% by weight, more preferably 0 to 5% by weight, when the agent is taken as 100% by weight. EXAMPLES
[0079] The present invention will now be described in more detail with reference to examples, which are not intended to limit the scope of the present invention. In the following, "%" indicates % by weight unless otherwise specified.
[0080] <Analysis method> Triglyceride composition The triacylglycerol content of fats and oils was measured by gas chromatography (AOCS C The symmetry of triacylglycerol was measured using a silver ion column chromatography. Chromatography method (J. High Resol. Chromatogr., 18, 105 -107(1995)). X-ray diffraction measurement Using an X-ray diffraction device Ultima IV (Rigaku Corporation), CuKα (λ=1. 542Å) radiation source, Cu filter used, output 1.6kW, operation angle 0.96~30. The measurement was performed at 0° and a measurement speed of 2° / min. If there is no peak in the vicinity of 4.1 to 4.2 Å, all of the fat and oil components are beta fat and oil. It was determined to be crystals. From the results of the above X-ray diffraction measurement, the peak intensity ratio = [β type characteristic peak intensity (2 θ=19°(4.6Å) / (Intensity of characteristic peaks of α type (and β' type) (2θ=21 β-type (2θ=19°(4.2Å)) + β-type characteristic peak intensity (2θ=19°(4.6Å))) It was measured as an index of the amount of fat crystals present. Loose bulk density The loose bulk density (g / cm3) of the powdered oil composition obtained in the examples was × 25mL measuring cylinder, about 2cm above the top opening of the measuring cylinder The powdered oil composition was dropped to fill the container loosely, and the weight (g) of the filled container was measured and the volume (mL) was read. The powdered oil composition was sampled and the weight (g) of the powdered oil composition per mL was calculated. Aspect Ratio Direct observation was performed using a scanning electron microscope S-3400N (Hitachi High-Technologies Corporation). Image analysis type particle size distribution measurement software (Mac-View made by Mountec Co., Ltd.) The length of the long axis and the length of the short axis of the arbitrarily selected particle are measured using The average number of counted particles was calculated. ·Average particle size (d50) Using a particle size distribution measuring device (Microtrac MT3300ExII manufactured by Nikkiso Co., Ltd.) Measurements were made based on the laser diffraction scattering method (ISO133201, ISO9276-1). Particle size is the diameter at which the larger and smaller particles are equal when a powder is divided into two particles of a certain size ( d50) value.
[0081] -Softening point of binder resin Using a flow tester (Shimadzu Corporation, CFT-500D), 1 g of sample is heated at a temperature increase rate of 6°C / min, while applying a load of 1.96 MPa with the plunger, and extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The plunger descent amount of the flow tester is plotted against the temperature, and the temperature at which half of the sample flows out is regarded as the softening point of the binder resin. · Glass transition temperature of binder resin Using a differential scanning calorimeter (TA Instruments Japan, Q-100), 0.01 to 0.02 g of the sample was weighed into an aluminum pan, heated to 200°C, and cooled to 0°C at a rate of 10°C / min. The sample was then measured at a heating rate of 10°C / min. The glass transition point of the binder resin was determined as the temperature at the intersection of an extension of the baseline below the highest endothermic peak temperature and a tangent line showing the maximum slope from the rising part of the peak to the top of the peak. - Acid value of binder resin Measure according to the method of JIS K0070, except that the measurement solvent is changed from the ethanol and ether mixture specified in JIS K0070 to a mixture of acetone and toluene (acetone:toluene = 1:1 (volume ratio)). Melting point and half-width of release agent Using a differential scanning calorimeter (TA Instruments Japan, DSC Q20), the sample is heated to 200°C at a heating rate of 10°C / min, cooled to 10°C at a heating rate of 5°C / min, and then heated to 180°C at a heating rate of 10°C / min. The highest endothermic peak temperature observed in the melting endothermic curve obtained at this point is taken as the melting point of the release agent. The peak width at the midpoint of the height from the baseline of the entire endothermic peak of the melting point to the peak top is defined as the half-value width of the release agent. - Melt viscosity of release agent The measurement is carried out by the Brookfield method using a Brookfield type viscometer (LVT, manufactured by ST Johnson Japan Ltd.), and the measurement sample is heated to 100° C., which is a temperature equal to or higher than the melting temperature of the release agent. Volume median particle size of toner (D 50 ) Measuring device: Coulter Multisizer II (manufactured by Beckman Coulter) Aperture diameter: 100μm Analysis software: Coulter Multisizer AccuComp version 1.19 (Beckman Coulter) Luther) Electrolyte: Isoton II (Beckman Coulter) Dispersion liquid: Emulgen 109P (Kao Corporation, polyoxyethylene lauryl ether, HLB: 13.6) is dissolved in the electrolyte to a concentration of 5% by weight. Dispersion conditions: 10 mg of the measurement sample is added to 5 ml of the dispersion liquid, and dispersed for 1 minute using an ultrasonic disperser. Then, 25 ml of the electrolyte is added, and further dispersed for 1 minute using an ultrasonic disperser to prepare a sample dispersion liquid. Measurement conditions: The sample dispersion was added to 100 ml of the electrolyte so that the particle size of 30,000 particles could be measured in 20 seconds. 30,000 particles were measured, and the volume median particle size (D 50 ) is required.
[0082] [Example of wax 1 production] 25 g of triglyceride having stearic acid residues (carbon number 18) at the 1st to 3rd positions (XXX type: 79.1% by weight, extremely hardened rapeseed oil (melting point 67.3°C), the extremely hardened rapeseed oil is obtained by hardening the raw material oil and fat under conditions of hydrogen pressure 0.1 to 0.3 MPa and 160 to 230°C under a nickel catalyst, and then blowing in 2 to 5% by weight of steam and performing a deodorization process at a temperature of 230 to 260°C under a reduced pressure of 200 to 600 Pa for 60 to 90 minutes) was maintained at 80°C for 0.5 hours to completely melt it, and cooled in a 60°C constant temperature bath for 12 hours to form a solid having voids with an increased volume, and after completing crystallization, it was cooled to room temperature (25°C). The obtained solid was mechanically pulverized to obtain powdered fat crystals (loose bulk density: 0.2 g / cm3, aspect ratio: 1.6, average particle size: 8.0 μm, X-ray diffraction measurement diffraction peak: 4.6 Å, peak intensity ratio: 0.89). This fat powder was named Wax 1.
[0083] Note that carnauba wax "C1" (manufactured by Kato Yoko, melting point: 80°C) was used as wax 2, and paraffin wax "HNP-9" (manufactured by Nippon Seiro, melting point 75°C) was used as wax 3. Both carnauba wax and paraffin wax are commonly used as waxes for toners.
[0084] [Production example of binder resin A] 1286g of polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, 2218g of polyoxyethylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, 1603g of terephthalic acid, 10g of tin(II) 2-ethylhexanoate, and 2g of gallic acid were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and reacted under a nitrogen atmosphere at 230°C until the reaction rate reached 90%, and then reacted at 8.3kPa until the softening point reached 108°C, to obtain binder resin A. The softening point of binder resin A was 108.9°C, the glass transition point was 67.4°C, and the acid value was 3.9mgKOH / g. The reaction rate refers to the value of the amount of reaction water produced / theoretical amount of water produced×100.
[0085] [Manufacturing example of binder resin B] 3486g of polyoxypropylene (2.2)-2,2-bis (4-hydroxyphenyl) propane, 3240g of polyoxyethylene (2.2)-2,2-bis (4-hydroxyphenyl) propane, 1881g of terephthalic acid, 269g of tetrapropenyl succinic anhydride, 30g of tin (II) 2-ethylhexanoate, and 2g of gallic acid were placed in a 10-liter four-neck flask equipped with a nitrogen inlet tube, a dehydration tube, a stirrer, and a thermocouple, and reacted under a nitrogen atmosphere at 230°C until the reaction rate reached 90%, and then reacted at 8.3kPa for 1 hour. Next, the temperature was lowered to 220°C to return to normal pressure, and 789g of trimellitic anhydride was added, and the reaction was continued under conditions of 220°C and normal pressure until the softening point reached 127°C, to obtain binder resin B. Binder resin B had a softening point of 126.1° C., a glass transition point of 64.5° C., and an acid value of 16.8 mgKOH / g.
[0086] [Toner manufacturing example] Example 1 and Comparative Examples 1 to 3 Binder resin A: 70 parts by weight, binder resin B: 30 parts by weight, negatively charged charge control agent "Bontron E-304" (manufactured by Orient Chemical Co., Ltd.): 1 part by weight, colorant "ECB-301" (manufactured by Dainichi Seikagaku Co., Ltd., phthalocyanine blue (PB15:3)): 3.5 parts by weight, and predetermined amounts of waxes 1 to 3 shown in Table 1 were mixed for 1 minute using a Henschel mixer, and then melt-kneaded under the conditions shown below.
[0087] For melt mixing, a co-rotating twin screw extruder PCM-30 (manufactured by Ikegai Iron Works) was used. The operating conditions of the co-rotating twin screw extruder were barrel temperature: 100°C, shaft rotation speed: 200 r / min (circumferential speed of shaft rotation: 0.30 m / sec), and mixture supply rate: 10 kg / hr.
[0088] The kneaded product thus obtained was cooled and coarsely crushed to 3 mm using a Rotoplex (manufactured by Toa Machinery Co., Ltd.), then crushed using a fluidized bed jet mill "AFG-400" (manufactured by Alpine Co., Ltd.), and classified using a rotor classifier "TTSP" (manufactured by Alpine Co., Ltd.) to obtain the volume median particle size (D 50Toner base particles having a particle diameter of 8.0 μm were obtained. 100 parts by weight of the obtained toner base particles were mixed with 1.0 part by weight of hydrophobic silica "RY50" (manufactured by Nippon Aerosil Co., Ltd.) and 0.5 part by weight of hydrophobic silica "R972" (manufactured by Nippon Aerosil Co., Ltd.) in a 20-liter Henschel mixer (manufactured by Mitsui Mining Co., Ltd.) at 1500 r / min (circumferential speed 21 m / sec) for 1 minute to obtain a toner.
[0089] Test Example 1 [Low temperature fixability] The toner was loaded into a copier "AR-505" (manufactured by Sharp Corporation) and an image was printed without fixing (print area: 2 cm x 12 cm, adhesion amount: 0.5 mg / cm2). The fixing temperature was raised from 90°C to 240°C in 5°C increments with the fixing machine of the copier offline, and the toner was fixed onto the paper at 400 mm / sec. The fixing paper used was "CopyBond SF-70NA" (manufactured by Sharp Corporation, 75 g / m2). "UNICEF Cellophane" (Mitsubishi Pencil Co., Ltd., width: 18 mm, JIS Z-1522) was attached to the fixed image, and after passing it through a fixing roller set at 30°C, the tape was peeled off. The optical reflection density before and after the tape was attached was measured using a reflection densitometer "RD-915" (Macbeth Co., Ltd.), and the minimum fixing temperature (low-temperature fixing ability) was evaluated as the fixing roller temperature at which the ratio of the two (after peeling / before attachment) first exceeded 90%. The results are shown in Table 1. The smaller the value, the better the low-temperature fixing ability.
[0090] Test Example 2 [Resistance to in-flight contamination] It is an oil-less fixing method that does not have a filter in the exhaust section and is a non-magnetic one-component development type printer. A linter "C5800" (manufactured by Oki Data Corporation) was placed in the chamber (volume W x H x D: 1000 x 1100 x 810 mm = 0.891 m3), and printing was performed for 2 hours at a printing rate of 5%. The air in the chamber was pumped through a glass fiber filter (manufactured by Pall Corporation, A / E type, 47 mmφ, pore size 1 μm) and collected at 50 L / min / cm2. The weight of the dispersed fine powder (dust) was measured, and the amount dispersed per hour (mg / h), i.e., the resistance to contamination inside the machine, was calculated. The results are shown in Table 1. The smaller the value, the better the resistance to contamination inside the machine.
[0091] [Table 1] *Part by weight relative to 100 parts by weight of binder resin *1 "Carnauba Wax C1" (Kato Yoko Co., Ltd., melting point: 80°C) *2 "HNP-9" (manufactured by Nippon Seiro Co., Ltd., melting point 75°C)
[0092] From the results in Table 1, it was found that the toner of Example 1 is equally excellent in low temperature fixing property compared to the toners of Comparative Examples 1 and 2. It was also found that the toner of Example 1 is exceptionally excellent in resistance to in-machine contamination compared to the toners of Comparative Examples 1 and 2. [Industrial Applicability]
[0093] The toner obtained by the method of the present invention is suitably used for developing latent images formed in electrophotography, electrostatic recording, electrostatic printing and the like.
Claims
[Claim 1] A method for producing a toner having excellent resistance to in-machine contamination, comprising the step of melt-kneading a binder resin and a release agent, wherein the release agent is an oil powder having 79.1% by weight or more of triglyceride having stearic acid residues at the 1st to 3rd positions, obtained by a process of hydrogenating rapeseed oil and passing through a hardening treatment process, followed by a deodorization process in which steam is blown in while the pressure is reduced and the mixture is heated, the melting point being 50°C or higher and less than 80°C, and the beta crystals having an average particle size (d50) of less than 30 μm.
Citation Information
Patent Citations
Electrophotographic toner
JP1996179547A
Wax composition used for toner for developing electrostatic charge image and its production
JP1996278657A
Ester wax for toner and toner using the same, developer, toner storage unit, and image forming apparatus
JP2017167524A
